Isolation and Characterization of Iridoid Glycoside (Gardenoside) Present in the Leaves of Gardenia jasminoides J.Ellis Cultivated in Iraq - Usama H. Abdul Wahab; Zainab J. Awad (College of Pharmacy University of Baghdad, 2017)
Iridoid glycosides are a group of naturally occurring chemical compounds. They are a large family of compounds biosynthesized by plants, they often have pharmacological effects. The aim of this study is to isolate and identified iridoid glycoside in a newly studied, cultivated in Iraq named Gardenis jasminoides. The medicinal importance of iridoid glycoside, on one hand and absence of phytochemical investigation on leaves of Gardenia on the other hand, acquired this study its importance. Many compounds were isolated from leaves plant part one of these compounds was identified by different chemical analysis like: melting point (MP), thin layer chromatography (TLC), Fourier transforms infrared spectra (FTIR) and high performance liquid chromatography (HPLC). Keywords: Gardenia jasminoides , Gardenoside,Geniposide,Genipin.